Edukasi Gerakan Masyarakat Hidup Sehat (Germas) Untuk Pencegahan Penyakit Tidak Menular di Desa Gribig Krajan Kabupaten Kudus - Ayu Denisa Wangsa Putri; Dyah Utari (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
The prevalence of non-communicable diseases in Indonesia is increasing from year to year. One of the causes is lack of activity behavior or a sedentary lifestyle. The purpose of this Community Service Program is to provide education on the importance of regular physical activity to prevent non-communicable diseases. Service is carried out through three stages, namely identification and analysis of problems, advocacy and providing education. The activity was carried out in Gribig Krajan Village, Gebog District, Kudus Regency, Central Java Province. Based on the results of the pre-test and post-test, it was found that there was an increase in the knowledge of the participants, which was 28.59% so that participants were expected to be able to apply it in their daily activities and be able to disseminate the information to the surrounding environment.